Equilibrium states for non-uniformly hyperbolic systems: Statistical properties and analyticity - Afonso, Suzete Maria [UNESP]; Ramos, Vanessa; Siqueira, Jaqueline (American Institute of Mathematical Sciences (AIMS), 2021)
We consider a wide family of non-uniformly expanding maps and hyperbolic Hölder continuous potentials. We prove that the unique equilibrium state associated to each element of this family is given by the eigenfunction of the transfer operator and the eigenmeasure of the dual operator (both having the spectral radius as eigenvalue). We show that the transfer operator has the spectral gap property in some space of Hölder continuous observables and from this we obtain an exponential decay of correlations and a central limit theorem for the equilibrium state. Moreover, we establish the analyticity with respect to the potential of the equilibrium state as well as that of other thermodynamic quantities. Furthermore, we derive similar results for the equilibrium state associated to a family of non-uniformly hyperbolic skew products and hyperbolic Hölder continuous potentials.
Keywords: Analyticity; Equilibrium states; Limit theorems; Non-uniform hyperbolicity; Partial hyperbolicity